PENINGKATAN USAHA PENGOLAHAN IKAN SEPAT (Trichogaster trichopterus pall) DI DESA SUNGAI RANGAS ULU KECAMATAN MARTAPURA KABUPATEN BANJAR - Rimalia, Anny; Zuraida, Zuraida (JURNAL PENGABDIAN PAPUA, 2023)
This Community Engagement aims to enhance the efforts of snakehead fish processing in Sungai Rangas Ulu Village, Martapura, Banjar Regency, South Kalimantan. It was achieved through training provided to groups of housewives. With the participation of 71.43% of the expected attendees, this study successfully imparted the necessary knowledge and skills to process snakehead fish into high-value products. Employing a methodology comprising lectures, demonstrations/ practical sessions, and question-and-answer sessions, participants comprehended and effectively applied the concepts of snakehead fish processing. It is evident that 95% of the planned content was effectively delivered to the participants. These results are reflected in the enthusiasm of the participants and the new skills they acquired in processing snakehead fish with various flavors such as durian, chocolate, melon, and mango. The research demonstrates an increase in knowledge regarding the diversification of processed food from snakehead fish, providing new opportunities for participants to enhance their income through more creative snakehead fish processing endeavors. Consequently, this engagement initiative has effectively yielded a positive impact in developing snakehead fish processing businesses, strengthening the potential of local products, and improving the welfare of the local community. Gratitude is extended to LP2M Achmad Yani University and the relevant parties for their support in executing this initiative. Keywords: Business Value Enhancement; Snakehead Fish Processing; Diversification